2017
DOI: 10.1016/j.cellsig.2017.05.012
|View full text |Cite
|
Sign up to set email alerts
|

The many faces of compartmentalized PKA signalosomes

Abstract: Cellular signal transmission requires the dynamic formation of spatiotemporally controlled molecular interactions. At the cell surface information is received by receptor complexes and relayed through intracellular signaling platforms which organize the actions of functionally interacting signaling enzymes and substrates. The list of hormone or neurotransmitter pathways that utilize the ubiquitous cAMP-sensing protein kinase A (PKA) system is expansive. This requires that the specificity, duration, and intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
150
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 162 publications
(170 citation statements)
references
References 180 publications
2
150
1
Order By: Relevance
“…Increased PKA activity is observed in cancer and PKA has been proposed as an important target for cancer treatment . Previous studies showed that cellular compartmentalized regulation of PKA activity is mainly achieved by A‐kinase anchoring proteins, a group of proteins interacting with PKA regulatory subunits, recruiting PKA to cellular specific loci, and directing PKA kinase activity to specific substrates . Using Co‐IF staining and Co‐IP experiments, we demonstrated that ITGA9 KO significantly increases the interaction between ILK and PKA.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Increased PKA activity is observed in cancer and PKA has been proposed as an important target for cancer treatment . Previous studies showed that cellular compartmentalized regulation of PKA activity is mainly achieved by A‐kinase anchoring proteins, a group of proteins interacting with PKA regulatory subunits, recruiting PKA to cellular specific loci, and directing PKA kinase activity to specific substrates . Using Co‐IF staining and Co‐IP experiments, we demonstrated that ITGA9 KO significantly increases the interaction between ILK and PKA.…”
Section: Discussionmentioning
confidence: 78%
“…40 Previous studies showed that cellular compartmentalized regulation of PKA activity is mainly achieved by A-kinase anchoring proteins, a group of proteins interacting with PKA regulatory subunits, recruiting PKA to cellular specific loci, and directing PKA kinase activity to specific substrates. 39,46,47 Using Co-IF staining and Co-IP experiments, we demonstrated that ITGA9 KO significantly increases the interaction between ILK and PKA. Although it remains to be determined whether ILK directly interacts with PKA regulatory subunit or catalytic subunit, this interaction reduces PKA activity.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Three PKA catalytic subunits (Cα, Cβ, and Cγ) and four regulatory subunits (RIα, RIβ, RIIα, and RIIβ) have been described in mammalian tissues, with different expression in the various tissues and developmental time course of appearance. Apparently, they are precisely docked at selected intracellular sites [ 1 ] and have different binding affinities for their ligands. [ 2 ] Each regulatory subunit binds two cAMP molecules, leading to the release of the catalytic subunit from the tetrameric complex, thus allowing phosphorylation of target proteins.…”
Section: Introductionmentioning
confidence: 99%